Implement pacts fully, say Najib and Susilo - Malay, Mail (Malay Mail, 2012)
PRIME MINISTER Datuk Seri Najib Razak and Indonesian President Susilo Bambang Yudhoyono have emphasised the importance for both countries to fully implement the provisions of the Protocol to Amend the Memorandum of Understanding on the Recruitment and Placement of Indonesian Domestic Workers 2006.